Supervisory control case study tolerant to intermittent observation losses: MECATRIME Plant (Research, Society and Development, 2022)
This paper presents a case study of supervisory control tolerant to intermittent loss of observation considering the existence of loss of communication between devices interconnected to the plant via LAN (local ETHERNET network), in a flexible manufacturing system existing at the Mechatronics Laboratory of the Military Engineering Institute (MECATRIME plant). This study aimed to apply supervisory control concepts when there are intermittent losses of observation when there is a communication failure and thus allow the system to continue acting. Initially, a mapping of the MECATRIME plant was made, in which diagrams based on Systems Engineering were constructed in order to identify the points or situations where there is the possibility of loss of observation due to the loss of communication and, after this mapping, system modeling was performed using state machine diagrams, in the form of automata, with intermittent loss of observation. The supervisor's synthesis was also made, showing how a formal tool can be used to guide the realization of the project of a control system tolerant to losses of observation by communication.